2021
DOI: 10.1136/bmjopen-2021-049443
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with ambulance use for non-emergency problems in children? A systematic mapping review and qualitative synthesis

Abstract: ObjectiveTo explore what factors are associated with ambulance use for non-emergency problems in children.MethodsThis study is a systematic mapping review and qualitative synthesis of published journal articles and grey literature. Searches were conducted on the following databases, for articles published between January 1980 and July 2020: MEDLINE, EMBASE, PsycINFO, CINAHL and AMED. A Google Scholar and a Web of Science search were undertaken to identify reports or proceedings not indexed in the above. Book c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This might have prevented the visits (and its attendant wasteful use of resources and increased burden on healthcare services) of about one-half (43.7%) of the febrile children that were diagnosed of acute uncomplicated malaria in the centers. This needless visit due to poor knowledge of childhood fever has also been reported in developed settings (55) including the non-urgent use of ambulances (56).…”
Section: Discussionmentioning
confidence: 64%
“…This might have prevented the visits (and its attendant wasteful use of resources and increased burden on healthcare services) of about one-half (43.7%) of the febrile children that were diagnosed of acute uncomplicated malaria in the centers. This needless visit due to poor knowledge of childhood fever has also been reported in developed settings (55) including the non-urgent use of ambulances (56).…”
Section: Discussionmentioning
confidence: 64%
“…18,24 Interestingly, another study presenting hypothetical non-emergency scenarios also found older people more likely to call for an emergency ambulance than younger people. 25 We noted those who had completed a university degree and had higher household income were less likely to call an ambulance for nonemergency scenarios (previous research also links heightened education with more appropriate ambulance use, 26 as were people with higher emotional wellbeing as measured via the BEES. Although several studies have investigated the impact of patients utilising EHS for acute mental health issues, few have investigated the association between poor mental and/or emotional wellbeing and potentially unnecessary use of EHS.…”
Section: Summary Of Findingsmentioning
confidence: 88%
“…These included socioeconomic status, geographical location, practical reasons (ie, lack of transport), emotional reasons (ie, uncertainty, reassurance) and level of education, knowledge and experience in judging the appropriateness of ambulance use for their circumstances. 17 18 Although a small-scale intervention may not radically change the behaviour of the population, better knowledge and awareness repeatedly consolidated by the use of educational apps may encourage individuals to evaluate their options more thoroughly before seeking emergency care. Quite possibly, interventions such as the Blue Light Hub app may have the most impact in more deprived areas; future research would do well to investigate this possibility on a larger scale and explore the generalisability of this type of education-based intervention in other locations and contexts.…”
Section: Discussionmentioning
confidence: 99%